Estudio de la estructuración de los vínculos de niños y niñas que viven en la calle “La Ronda” a partir de la transformación del uso del espacio público - Vásquez Pérez, Diego Fernando (2013)
This research is the understanding of the linkages that develop in children who reside in “La Ronda” neighborhood from the transformation of the use of space, in order to deploy this understanding took a qualitative methodology was made non-experimental, since no manipulated variables. Phenomenon was observed as it develops, for at a later time can be analyzed, and as one of the main tools of analysis used the playful workshops realized in the community. Each workshop is conceived as representing micro space, which is understood as macro space to the neighborhood “La Ronda” and its dynamics, and through them, knowing the type of link that develops between children of the site, meaning link, the process of introjection of the external environment and projection manifested through behaviors in a constant dialectical interaction. The behavior that is evident in the children of “La Ronda” neighborhood in the various dynamics of the workshop, it are generally aggressive towards members, because the others are perceived as bad, like a strong “Id” that It can destroy the weak “Ego” and a “Super Ego” with too strict rules that limit and not allow free link. Given these dynamics not possible that children who live in the “La Ronda” are identified and therefore cannot generate an appropriation of the use of space